Low Incubation Temperature During Late Incubation and Early Feeding Affect Broiler Resilience to Necrotic Enteritis in Later Life - Wijnen, Hendrikus J.; van der Pol, Carla W.; van Roovert-Reijrink, Inge A. M.; De Smet, Joren; Lammers, Aart; Kemp, Bas; van den Brand, Henry; Molenaar, Roos (Frontiers in Veterinary Science, 2021)
Resilient animals can cope with environmental disturbances in life with minimal loss of function. Resilience can be enhanced by optimizing early life conditions. In poultry, eggshell temperature (EST) during incubation and early feeding are two early life conditions that are found to alter neonatal chick quality as well as immune response in later life. However, it has never been studied yet these early life conditions affect disease resilience of chickens at later ages. Hence, we studied effects of EST ( 37.8°C (control) or 36.7°C (lower)) during late incubation (≥embryonic day 17- 19.5) and feeding strategy after hatch (immediately (early feeding) or 51-54 h delayed (delayed feeding)) on later life broiler resilience in a 2 x 2 factorial arrangement. At hatch, 960 broilers of both sexes from a 54 wk old Ross breeder flock were equally divided over 32 pens (8 replicate pens / treatment combination) and grown for 6 wks. Necrotic enteritis was induced by a single inoculation of Eimeria spp. at d 21 and repeated Clostridium perfringens inoculation (3x /d) during d 21 - 25. Mortality and BW gain were measured daily during d 21 – 35 as indicators of resilience. Additionally, disease morbidity was assessed (gut lesions, dysbacteriosis, shedding of oocysts, footpad dermatitis, and natural antibody levels in blood). Results showed a lack of interaction between EST and feeding strategy for the vast majority of the variables. A lower EST resulted in lower BW gain at d 5 and 8 post Eimeria inoculation (P=0.02) and more E. Maxima oocysts in feces at d 8 post Eimeria inoculation compared to control EST (P<0.01). Early feeding tended to lower mortality compared to delayed feeding (P=0.06) but BW gain was not affected by feeding strategy. Morbidity characteristics were hardly affected by EST or feeding strategy. In conclusions, a few indications were found that a lower EST during late incubation as well as delayed feeding after hatch each may impair later life resilience to necrotic enteritis. However, these findings were not manifested consistently in all parameters that were measured and conclusions are drawn with some restraint.